Does Earnings Quality Mediate The Effect Of Corporate Governance On Firm Value - Kodriyah; Nana Umdiana; Denny Putri Hapsari; Santi Octaviani (Publisher Cv. Inara, 2021)
This study aims to examine the influence of corporate governance factors on firm value and earnings quality as mediating variables. Research Methodology Using Purposive Sampling techniques, so as to obtain a data of 102. The analysis technique used was to use multiple regression and path analysis. Indicator of corporate governance has effect on firm value are managerial ownership and audit committee. Indicator of corporate governance has effect on earnings quality are Institutional ownership and audit committee. The earnings quality has no significant effect on the value of the company and has not been able to mediate the influence of managerial ownership, institutional ownership and committee on the value of the company. The corporate governance indicator is used 3 while there are other indicators such as the proportion of the independent commissioners board and the proportion of the board of directors. Investors do not only look at the financial aspects but can also see other information such as the implementation of corporate governance mechanisms as one of the considerations for investment decisions